Negative Affect, Alcohol Consumption, and Female-to-Male Intimate Partner Violence: A Daily Diary Investigation - Crane, Cory (Partner Abuse, 2013)
While research suggests that both negative affect and alcohol use are related to the risk of intimate partner violence (IPV) in male samples, less is known about the status of these risk factors in female samples. Forty-three college-age females who reported a recent history of IPV perpetration submitted six weeks of on-line daily reports pertaining to their levels of negative affect, alcohol consumption habits, and the occurrence of both male-to-female (MFPV) and female-to-male IPV (FMPV). Results indicated that negative affect significantly predicted increases in the daily risk of FMPV. MFPV also significantly predicted FMPV risk. Alcohol consumption failed to predict FMPV perpetration on both levels of analysis. Results are discussed in terms of prevailing models of alcohol use, negative affect, and IPV.